'If I get a good job you could say that it was worthwhile': students' views on higher education as a risk investment. Issue 2 (3rd April 2022) - Lolich, Luciana
Abstract : Students' choices in higher education occupy a wide spectrum in recent academic and policy discussions. However, there has been little research on how government discourses on the knowledge-based economy shape, transform or influence students' choices at a micro-level. This paper uses a governmentality framework to link the ways in which the 'conduct of conduct' operates through the episteme, techne and ethos of government. The paper presents findings from a large-scale survey in three major higher education institutions in Ireland, together with the thematic analysis of students' comments on an open-ended question. The findings show that students invest heavily in more advanced HE qualification in order to perform well in the competition for jobs. However, the study also demonstrates that students are aware of the limitations in this human capital framework but not due to them making bad choices but to the lack of control individuals have in affecting the labour market.